Inhaled corticosteroid is not associated with a poor prognosis in COVID‐19. Issue 8 (26th June 2021) - An, Tai Joon; Kim, Youlim; Park, Yong Bum; Kim, Kyungjoo; Cho, Do Yeon; Yoo, Kwang‐Ha; Rhee, Chin Kook
Abstract : Inhaled corticosteroid is not associated with a poor prognosis in COVID‐19